Increasing the Thermostability of Optoelectronic Devices on Semiconductor Radiators - et.al, DalievKhojiakbarSultanovich (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article proposes a scheme for thermal stabilization of the radiation flux of mid-IR LEDs in the temperature range + 20 ° C + 80 ° C. It is shown that the relevance of mid-IR LEDs for solving problems of gas analysis, environmental monitoring, moisture measurement and medical diagnostics. It was revealed that the guarantee of the measurement accuracy and sensitivity of optoelectronic devices is the correct spectral matching of the photodetector, LED and absorption of the investigated substance. The disadvantages of emitting diodes associated with time and temperature instability during operation are considered. A study of the spectral characteristics of mid-IR LEDs at various temperatures showed that the wavelength at the maximum the emission spectrum increases almost linearly with increasing temperature, which leads to additional errors and lowers the measurement accuracy of optoelectronic devices. A schematic diagram is proposed for stabilizing the radiation flux of mid-IR LEDs in the temperature range + 20 ° C + 80 ° C..